A Review on Nutrient Quality of Soymilk Powder for Malnourished Population - Mazumder, Md. Anisur Rahman; Hongsprabhas, Parichat (Pakistan Journal of Nutrition, 2016)
This study was conducted to find out the nutritional factors that can help the developing countries to reduce malnutrition problem through use of spray dried soymilk powder. The main advantage of powdered milk is the reduction of bulk volume. It results extension of the storage life, stability of the appropriately packaged product, saving of storage and transportation costs. Soy protein is an important source of high-quality protein for a long time. The present article focuses on nutritional and non-nutritional such as phytochemicals aspects of soymilk powder and the probable use of soymilk powder as a source of protein, vitamins and minerals for malnourished people. Soy powder contained considerable amount of essential and branched chain amino acids except methionine and a good source of B-vitamins particularly niacin, pyridoxine and folacin. Nonetheless, a growing number of calcium-fortified soymilks are available. However, soy powder is rich in copper, zinc and magnesium.